Mechanisms and Management of Acute Pancreatitis. (15th March 2018) - Garber, Ari; Frakes, Catherine; Arora, Zubin; Chahal, Prabhleen
Abstract : Acute pancreatitis represents a disorder characterized by acute necroinflammatory changes of the pancreas and is histologically characterized by acinar cell destruction. Diagnosed clinically with the Revised Atlanta Criteria, and with alcohol and cholelithiasis/choledocholithiasis as the two most prominent antecedents, acute pancreatitis ranks first amongst gastrointestinal diagnoses requiring admission and 21st amongst all diagnoses requiring hospitalization with estimated costs approximating 2.6 billion dollars annually. Complications arising from acute pancreatitis follow a progression from pancreatic/peripancreatic fluid collections to pseudocysts and from pancreatic/peripancreatic necrosis to walled-off necrosis that typically occur over the course of a 4-week interval. Treatment relies heavily on fluid resuscitation and nutrition with advanced endoscopic techniques and cholecystectomy utilized in the setting of gallstone pancreatitis. When necessity dictates a drainage procedure (persistent abdominal pain, gastric or duodenal outlet obstruction, biliary obstruction, and infection), an endoscopic ultrasound with advanced endoscopic techniques and technology rather than surgical intervention is increasingly being utilized to manage symptomatic pseudocysts and walled-off pancreatic necrosis by performing a cystogastrostomy.